A numerical taxonomic study of Trapa from China - HU Ren-yong; DING Bing-yang; HUANG Tao; ZHENG Chao-zong (浙江大学学报. 农业与生命科学版, 2001)
37 populations of Trapa L. from the 12 provinces of China were studied by means of numerical taxonomic methods. The results are as follows: ①Q cluster analysis is shown that 37 populations can be divided into 3 groups. The first group have only one species of T. maximowiczii, the second include other wild types except T. maximowiczii, the third are the cultivated kinds. ② result obtained through R cluster analysis is conductive to the relationships among the 31 characters. ③ result obtained through principal component analysis (PCA) shows the loading of 37 populations is a unanimous conclusion with Q cluster analysis. ④ Finally, 37 populations of Chinese Trapa L. are divided into 2 species based on the characters of the size and shape of nuts (T. maximowiczii and T. incisa complex), the characters of upper horns and the others may be the foundation of divided varieties.